Adapting a Business Communication Course to the Market Needs - Diana Christine Zelter (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
This paper will represent a practical approach to re-designing course curriculum and syllabus in order to fit the needs of the job market. The course in question "Business Communication" is taught to 3rd year students in our Faculty of Economics and Business Administration, belonging to the Babeş-Bolyai University from Cluj-Napoca, Romania. The course has been in place for many years; however, lately, we have thought that changes are necessary. These changes are determined by the changing needs of the job market as more and more multinational companies have set up offices in our city. The paper will present the basis for these changes, i.e. how we identified the market needs (qualitative research: meetings/discussions with managers/recruiters from multinationals) and what improvements we intend to bring to the syllabus of the course in order to focus more on the skills employees need in their workplace. At the same time, we would like to show the correlation between business communication skills and language skills (the course is taught in 5 different languages) as they are seen both by students and potential employers (quantitative and qualitative research: survey and focus group) and how this correlation could fit into the new course syllabus.
Keywords: 650; Business; Communication; Job Market; Students; Syllabus